Human entorhinal cortex electrical stimulation evoked short‐latency potentials in the broad neocortical regions: Evidence from cortico‐cortical evoked potential recordings. Issue 9 (30th July 2019) - Takeyama, Hirofumi; Matsumoto, Riki; Usami, Kiyohide; Nakae, Takuro; Kobayashi, Katsuya; Shimotake, Akihiro; Kikuchi, Takayuki; Yoshida, Kazumichi; Kunieda, Takeharu; Miyamoto, Susumu; Takahashi, Ryosuke; Ikeda, Akio
Abstract: Objective: We aimed at clarifying the clinical significance of the responses evoked by human entorhinal cortex (EC) electrical stimulation by means of cortico‐cortical evoked potentials (CCEPs). Methods: We enrolled nine patients with medically intractable medial temporal lobe epilepsy who underwent invasive presurgical evaluations with subdural or depth electrodes. Single‐pulse electrical stimulation was delivered to the EC and fusiform gyrus (FG), and their evoked potentials were compared. The correlation between the evoked potentials and Wechsler Memory Scale‐Revised (WMS‐R) score was analyzed to investigate whether memory circuit was involved in the generation of the evoked potentials. Results: In most electrodes placed on the neocortex, EC stimulation induced unique evoked potentials with positive polarity, termed as "widespread P1" (P1w). Compared with FG stimulation, P1w induced by EC stimulation were distinguished by their high occurrence rate, short peak latency (mean: 20.1 ms), small peak amplitude, and waveform uniformity among different recording sites. A stimulation of more posterior parts of the EC induced P1w with shorter latency and larger amplitude. P1w peak amplitude had a positive correlation ( r  = .69) with the visual memory score of the WMS‐R. In one patient, with depth electrode implanted into the hippocampus, the giant evoked potentials were recorded in the electrodes of the anterior hippocampus and EC near the stimulus site. Conclusions: The human EC electrical stimulation evoked the short‐latency potentials in the broad neocortical regions. The origin of P1w remains unclear, although the limited evidence suggests that P1w is the far‐field potential by the volume conduction of giant evoked potential from the EC itself and hippocampus. The significance of the present study is that those evoked potentials may be a potential biomarker of memory impairment in various neurological diseases, and we provided direct evidence for the functional subdivisions along the anterior–posterior axis in the human EC. Abstract : We found that the human EC electrical stimulation via subdural electrode evoked the short‐latency potentials in the broad neocortical regions. The most plausible generator mechanism of those responses is the far‐field potential from the medial temporal lobe memory circuit, especially from the EC itself and the hippocampus. The significance of the present study is that those evoked potentials may be a potential biomarker of memory impairment in various neurological diseases, and we provided direct evidence for the functional subdivisions along the anterior–posterior axis in the human EC.